Power Measurement System Prototype Design Used in Household Loads with The Arduino - Noorly Evalina; Dewi Sholeha; Faisal Irsan Pasaribu (Journal of Electronics, Telecommunication, Electrical, and Physics Science, 2022)
Modernization is indeed very influential in people's lives today, with the existence of this modern era everything is always related to technology. Apart from that, the use of household appliances and electricity also follows in accordance with existing developments, as seen by the development of prepaid electricity meters, which are all digital. However, with this existence, the community has not been able to control and monitor the use of electric power in detail. From the description of the problem above, the researcher found an idea to make a prototype Electric Power Monitoring tool that can work automatically. This tool uses an Arduino microcontroller coupled with a PZEM-004T Current, sensor, and along with an LCD. The way this tool works is to detect incoming electrical arcs, input from a load of electrical equipment on the PZEM 004T sensor, then systemically the sensor will receive the incoming arcs then the anus is directed to the microcontroller module. Arduino to convert systemically with the calculation of the power formula (Wh) Wh = Ixt (Ares x time) so that it will get the results of the electric power used during use in the form of current, days, voltage, cosphi, and KWH costs.